Assessing facial recognition after orthognathic surgery at automated border controls in airports. Issue 6 (July 2019) - Keshtgar, S.; Keshtgar, A.; Mistry, P.; Shakib, K.
Abstract: The aim of this paper was to find out whether orthognathic surgery affects facial recognition at automated border controls in airports, and whether we should recommend that patients update their photographic identification postoperatively. We collected data on all 82 patients who had orthognathic surgery between August 2013 and June 2017. They were contacted by telephone and asked about any difficulties they had encountered when passing through automated or human-operated border controls or when using other forms of photographic identification such as driving licences. All questions were asked with reference to experiences before the operation. A total of 50 patients responded, of which 35 had travelled by aeroplane since their operations. Six of them had had problems passing through passport control (two human-operated and four automated) but after additional security checks had successfully continued their journeys. Four had had bimaxillary surgery, one had had maxillary advancement, and one mandibular advancement. Orthognathic surgery does affect identification at border controls, and most of our patients had had difficulties at automated checks because of the differences between the biometric data within the e-passport chip and the live biometric that was scanned. These findings will enable us to improve the information we give to our patients before operation, but further studies are required to increase the sample size and improve reliability.